2017
DOI: 10.1017/s1041610217000898
|View full text |Cite
|
Sign up to set email alerts
|

A mismatch between supply and demand of social support in dementia care: a qualitative study on the perspectives of spousal caregivers and their social network members

Abstract: Background:Access to social support contributes to feelings of independence and better social health. This qualitative study aims to investigate multi-informant perspectives on informal social support in dementia care networks.Methods:Ten spousal caregivers of people with dementia (PwD) completed an ecogram, a social network card and a semi-structured interview. The ecogram aimed to trigger subjective experiences regarding social support. Subsequently, 17 network members were interviewed. The qualitative analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
63
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(65 citation statements)
references
References 35 publications
2
63
0
Order By: Relevance
“…We found that it is important to involve the social network, as it can play an important role in assisting with care tasks. Previous research has shown that informal carers often feel reluctant to ask their social network for support (Dam, Boots, van Boxtel, Verhey, & de Vugt, ). Healthcare professionals should pay attention to help carers to motivate and mobilise their social network and decrease barriers to ask for support, for example through family meetings.…”
Section: Discussionmentioning
confidence: 99%
“…We found that it is important to involve the social network, as it can play an important role in assisting with care tasks. Previous research has shown that informal carers often feel reluctant to ask their social network for support (Dam, Boots, van Boxtel, Verhey, & de Vugt, ). Healthcare professionals should pay attention to help carers to motivate and mobilise their social network and decrease barriers to ask for support, for example through family meetings.…”
Section: Discussionmentioning
confidence: 99%
“…Caregivers are often hesitant to ask for help because they are afraid of burdening others or assume that people are reluctant to help. However, people around them are actually often willing to provide support but do not know how they can contribute or are afraid to violate their privacy or stigmatize the situation (Dam, Boots, Verhey, Boxtel and de Vugt, in press). Therefore, it is important that caregivers express their needs and experiences.…”
Section: Discussionmentioning
confidence: 99%
“…There has been much research suggesting the beneficial implications for social support in both military and caregiver populations (Dam et al, ; S. Wilcox, ). Dam, Boots, van Boxtel, Verhey, and de Vugt () found multiple themes emerging related to supply and demand of social support among caregivers, including barriers and facilitators in asking for help, barriers and facilitators in offering support, mismatch between support supply and demand, and openness to repair the supply‐demand imbalance. Challenges to consider include maintaining connections beyond the intervention.…”
Section: Discussionmentioning
confidence: 99%